3 Phase Ac Servomotor Switching System. Issue 1 (February 2021) - Syafruddin, R; Sufyani, Rosyidin; Afiyah, Salamatul; Azhari, Mohammad Chusnul; Ramady, Givy Devira
Abstract: The background of the research is the need for switching ac 3 phase servomotor systems for precise position control purposes, in a fairly short displacement step with ac motor actuators. For this purpose, researchers controlled the direction of torque rotation of the servomotor magnetic field by controlling the switching system of the ac 3 phase bridges. The resultant torque of the resulting stator magnetic field represents the desired motor shaft position. For switching systems, we use space vector pulse wide modulation, with the consideration that the switching step is only 8 steps, where 2 steps are the high voltage short circuit arm step and the low voltage short circuit arm. Because the response of the motion is fast enough, the actuator used must be a winding rotor or permanent magnet rotor, better known as servomotor, for the cage rotor ac motor there are obstacles, where the motor loses torque, due to insufficient magnetic field generated by the rotor to move the rotor shaft in time quite short.